2015
DOI: 10.1590/0034-7167.2015680622i
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia das restrições hídrica e dietética em pacientes renais crônicos em hemodiálise

Abstract: these results can contribute to the nursing educational support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 10 publications
1
15
0
9
Order By: Relevance
“…In this sense, the Brazilian Society of Nephrology warns that being above 40 years is a relevant risk factor for the occurrence of chronic diseases, since there is a decrease in GFR of 0.08 ml/year after 40 years old, making the person vulnerable to electrolyte and metabolic imbalances (18)(19) . Other studies have also shown similar results in relation to the predominance of men (6,18,(20)(21)(22) .…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In this sense, the Brazilian Society of Nephrology warns that being above 40 years is a relevant risk factor for the occurrence of chronic diseases, since there is a decrease in GFR of 0.08 ml/year after 40 years old, making the person vulnerable to electrolyte and metabolic imbalances (18)(19) . Other studies have also shown similar results in relation to the predominance of men (6,18,(20)(21)(22) .…”
Section: Discussionsupporting
confidence: 71%
“…In this context, and considering the results obtained in the CT, the literature points out that the excessive intake of sodium predisposes the patient to excess fluid intake. This is associated with the mechanism of regulation of these elements, and this behavioral pattern directly influences the human response (20) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Além disso, as restrições hídricas e dietéticas são alguns dos contribuintes para o desenvolvimento da anorexia 20 . Estão inclusas nestas restrições a redução de sal, líquido, potássio e fósforo, revelando-se um grande desafio para o paciente e sua família [20][21][22] . Além disso, as inflamações crônicas induzidas por citocinas pró-inflamatórias observadas em pacientes com IRC, contribuem para a inapetência e consequente desnutrição e anorexia 15,18 .…”
Section: Discussão Anorexiaunclassified